2014
DOI: 10.1055/s-0034-1395157
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell–Derived Heparin Proteoglycans As a Model for a Local Antithrombotic

Abstract: Mast cell?derived heparin proteoglycans (HEP-PG) reside in vascular tissue and serve as a local antithrombotic. Heparin, as used clinically, is isolated from its protein backbone from porcine and bovine gut mucosa. The isolated heparin is an anticoagulant; however, when bound to a protein carrier the heparin conjugates will become antiplatelet agents by inhibiting collagen-induced platelet aggregation and procoagulant activity, as distinct from soluble heparin. HEP-PG, whether soluble or immobilized to a surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 23 publications
4
20
0
Order By: Relevance
“…To determine the effect of G6b-B clustering in solution, we took advantage of APAC, which mimics naturally occurring macromolecular heparin proteoglycans and harboring a higher GAG density than perlecan. Similar to previous reports (Kauhanen, Kovanen, & Lassila, 2000; Lassila & Jouppila, 2014; Lassila et al, 1997), we found that APAC inhibited platelet activation via the ITAM-containing GPVI-FcR γ-chain receptor complex, but also towards the hemi-ITAM-containing receptor CLEC-2. Thus, by increasing the clustering capacity of heparin to a multivalent form, an inhibitory effect on platelet function was achieved in solution.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…To determine the effect of G6b-B clustering in solution, we took advantage of APAC, which mimics naturally occurring macromolecular heparin proteoglycans and harboring a higher GAG density than perlecan. Similar to previous reports (Kauhanen, Kovanen, & Lassila, 2000; Lassila & Jouppila, 2014; Lassila et al, 1997), we found that APAC inhibited platelet activation via the ITAM-containing GPVI-FcR γ-chain receptor complex, but also towards the hemi-ITAM-containing receptor CLEC-2. Thus, by increasing the clustering capacity of heparin to a multivalent form, an inhibitory effect on platelet function was achieved in solution.…”
Section: Discussionsupporting
confidence: 92%
“…APAC consists of unfractionated heparin covalently coupled to a human albumin core, providing a high local density of heparin molecules. In contrast to single-chain heparin, APAC dose-dependently inhibited collagen-induced platelet aggregation (Figure 10), with an almost complete block observed at 0.5 μM, as previously described (Lassila & Jouppila, 2014).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Several biochemical and functional studies in humans and other species suggest that MCs represent the major source of heparin 9 , 154 , 158 , 221 . It has also been reported that MC-deficient Kit W/Wv mice develop more severe thromboembolic events after India ink injection compared to their normal littermates, and that injection of heparin can rescue these mice from fatal thromboembolic events 222 .…”
Section: Potential Role Of Mcs As Repair Cells In Thromboembolic Disomentioning
confidence: 99%